Nine black robes : inside the Supreme Court's drive to the right and its historic consequences [compact disc, unabridged] - Biskupic, Joan (Harper Audio, 2023)
CNN Senior Supreme Court Analyst Joan Biskupic provides an urgent and inside look at the history-making era in the Supreme Court during the Trump and post-Trump years, from its seismic shift to the Right to its controversial decisions, including its reversal of Roe v. Wade, based on access to all the key players.